Impacts of COVID-19 on Pregnancy Outcomes: A Retrospective Study - Donna Mendez; Krishna Paul; Jerome L. Yaklic; Dietrich Jehle (Emergency Care and Medicine)
Background: This study compared outcomes of pregnant females with and without COVID-19 and their fetuses/newborns. Methods: This is a retrospective study from 2020 to 2023 utilizing the United States Collaborative Network of the TriNetX Database. We compared the outcomes of pregnant females with COVID-19 and pregnant females without COVID-19. Maternal outcomes evaluated were death, intubation, intensive care unit (ICU) admission, and premature rupture of membranes (PROM) within 9 months of the diagnosis of pregnancy. Fetal outcomes included preterm birth and intrauterine death (IUD). A subgroup analysis of outcomes was performed based on the mother’s vaccine status. Results: The risks of maternal death (RR = 1.97), maternal intubation (RR = 3.33), and maternal (ICU) admission (RR = 1.76) were significantly higher in pregnant females with COVID-19. For the neonate, there was a higher risk of preterm birth (RR = 1.12). When the confounders were eliminated with propensity matching, there was still an increase in maternal intubation (RR = 3.24) and maternal ICU admission (RR = 1.60). For the neonate/fetus, there was a decreased risk of PROM (RR = 0.83) and IUD (RR = 0.74) for the fetuses of the mothers with COVID-19. For the subgroup analysis, the mother was at an increased risk of ICU admission (RR = 0.04) when unvaccinated. Conclusions: There is an increased risk of poor outcomes for pregnant women infected with COVID-19; however, fetal outcomes are generally favorable. When unvaccinated, there was an increased risk of ICU admission for the mother.